Algorithmic Influence and American Public Diplomacy: Ethical Dimensions of AI-Powered Political Advocacy on Social Media - Erfiyanto, Ruri; Santoso, Made Panji Teguh (Terekam Jejak Publisher, 2025)
This article investigates the ethical dimensions of artificial intelligence (AI)-powered political advocacy within the realm of U.S. public diplomacy, particularly as disseminated through social media platforms. The study applies a qualitative content analysis method, drawing from reputable media and academic sources, and is anchored in Networked Public Diplomacy Theory and Soft Power Theory. Findings indicate that while AI technologies enhance message personalization, efficiency, and reach, they also introduce significant ethical challenges including algorithmic bias, opacity, and the erosion of public trust. These risks threaten the legitimacy and credibility of diplomatic institutions, especially when AI-generated content lacks contextual awareness or factual rigor. The study reveals that although AI can support soft power projection, its uncritical use may distort democratic discourse and undermine long-term diplomatic objectives. The research concludes that AI must be embedded within transparent, accountable, and culturally sensitive frameworks to fulfill its potential as a tool for relational diplomacy. It also recommends methodological diversification and greater interdisciplinary engagement to address the complex socio-technical implications of AI in public diplomacy.